Biodiversity hotspots distribution and protection of conservation priority areas - Zachos, Frank E.; Habel,Jan Christian (Springer eBooks., 2011)
Biodiversity and its conservation are among the main global topics in science and politics and perhaps the major challenge for the present and coming generations. This book written by international experts from different disciplines comprises general chapters on diversity and its measurement, human impacts on biodiversity hotspots on a global scale, human diversity itself and various geographic regions exhibiting high levels of diversity. The areas covered range from genetics and taxonomy to evolutionary biology, biogeography and the social sciences. In addition to the classic hotspots in the tropics, the book also highlights various other ecosystems harbouring unique species communities including coral reefs and the Southern Ocean. The approach taken considers, but is not limited to, the original hotspot definition sensu stricto and presents a chapter introducing the 35th hotspot, the forests of East Australia. While, due to a bias in data availability, the majority of contributions on particular taxa deal with vertebrates and plants, some also deal with the less-studied invertebrates. This book will be essential reading for anyone involved with biodiversity, particularly researchers and practitioners in the fields of conservation biology, ecology and evolution.